Developing A "Polysulfide‐Phobic" Strategy to Restrain Shuttle Effect in Lithium–Sulfur Batteries. (19th July 2019) - He, Yibo; Qiao, Yu; Chang, Zhi; Cao, Xin; Jia, Min; He, Ping; Zhou, Haoshen
Abstract: Inspired by hydrophobic interface, a novel design of "polysulfide‐phobic" interface was proposed and developed to restrain shuttle effect in lithium–sulfur batteries. Two‐dimensional VOPO4 sheets with adequate active sites were employed to immobilize the polysulfides through the formation of a V−S bond. Moreover, owing to the intrinsic Coulomb repulsion between polysulfide anions, the surface anchored with polysulfides can be further evolved into a "polysulfide‐phobic" interface, which was demonstrated by the advanced time/space‐resolved operando Raman evidences. In particular, by introducing the "polysulfide‐phobic" surface design into separator fabrication, the lithium–sulfur battery performed a superior long‐term cycling stability. This work expands a novel strategy to build a "polysulfide‐phobic" surface by "self‐defense" mechanism for suppressing polysulfides shuttle, which provides new insights and opportunities to develop advanced lithium–sulfur batteries. Abstract : Eine „Polysulfid‐phobe" Strategie wurde entwickelt, um den Shuttle‐Effekt in Li‐S‐Batterien einzudämmen. Aufgrund der intrinsischen Elektronegativität der Polysulfidanionen können Polysulfid‐modifizierte polare Materialien eine „Polysulfid‐phobe" Oberfläche ausbilden, die eine starke Abstoßung auf freie Polysulfidanionen ausübt. Operando‐Raman‐Messungen belegen das Prinzip.